Dissent voices of conscience - Wright, Ann 1946-; Dixon, Susan L. (Koa Books, 2008)
During the run-up to war in Iraq, Army Colonel (Ret.) and diplomat Ann Wright resigned her State Department post in protest. Wright, who had spent 19 years in the military and 16 years in diplomatic service, was one among dozens of govern-ment insiders and active-duty military personnel who spoke out, resigned, leaked documents, or refused to deploy in protest of government actions they felt were illegal. In Dissent: Voices of Conscience, Ann Wright and Susan Dixon tell the stories of these men and women, who risked careers, reputations, and even freedom out of loyalty to the Constitution and the rule of law.